Serum Free Immunoglobulins Light Chains: A Common Feature of Common Variable Immunodeficiency? - Guevara-Hoyer, Kissy; Ochoa-Grullón, Juliana; Fernández-Arquero, Miguel; Cárdenas, Mariacruz; Pérez de Diego, Rebeca; Sánchez-Ramón, Silvia (Frontiers in Immunology, 2020)
Serum free light chain (sFLC) is a recently proposed biomarker for CVID diagnosis. Most CVID patients present low or undetectable sFLC up to 10-fold lower compared to other primary antibody deficiencies. Given that κ and λ light chains are normally secreted in excess with respect to immunoglobulins, this finding points to an intrinsic defect of B cell differentiation in CVID. sFLC levels were prospectively evaluated in a cohort of 100 primary immunodeficiency (PID) patients and in 49 patients with secondary immunodeficiency to haematological malignancy (SID). CVID patients had significantly lower κ and/or λ values (mean: κ: 1.39 ± 1.7 mg/L and λ: 1.97 ± 2.24 mg/L) compared to “other PIDs” (κ: 13.97 ± 5.88 mg/L and λ: 12.92 ± 7.4 mg/L, respectively, p < 0.001 both), and SID (κ 20.9 ± 22.8 mg/L and λ 12.8 ± 8.7 mg/L, respectively, p < 0.001 both). The sum of kappa and lambda (sum κ + λ) in CVID patients (7.25 ± 7.90 mg/L) was significantly lower respect to other PIDs (26.44 ± 13.25 mg/L, p < 0.0001), and to SID patients (28.25 ± 26.24 mg/L, p = 0.0002). ROC analysis of the sum κ + λ disclosed an area under the curve (AUC) of 0.894 for CVID diagnosis (SD 0.031; 95% CI: 0.83–0.95, p < 0.0001), with optimal cut-off of 16.7 mg/L, giving the highest combination of sensitivity (92%), specificity (75%) and NPV (98%). The Relative Risk (RR) for patients presenting a sum κ + λ below 16.7 mg/L was 20.35-fold higher (95%, CI: 5.630–75.93) for CVID than below this threshold. A similar behavior of the sFLC in our CVID cohort with respect to previously published studies was observed. We propose a cut-off of sum κ + λ 16.7 with diagnostic application in CVID patients, and discuss potential specific defects converging in low or undetectable sFLC.